2018
DOI: 10.1186/s13012-018-0823-9
|View full text |Cite|
|
Sign up to set email alerts
|

Improving care at scale: process evaluation of a multi-component quality improvement intervention to reduce mortality after emergency abdominal surgery (EPOCH trial)

Abstract: BackgroundImproving the quality and safety of perioperative care is a global priority. The Enhanced Peri-Operative Care for High-risk patients (EPOCH) trial was a stepped-wedge cluster randomised trial of a quality improvement (QI) programme to improve 90-day survival for patients undergoing emergency abdominal surgery in 93 hospitals in the UK National Health Service.MethodsThe aim of this process evaluation is to describe how the EPOCH intervention was planned, delivered and received, at both cluster and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 51 publications
0
113
0
Order By: Relevance
“…Our findings reveal that implementation of such an extensive care pathway was a more complex challenge than expected by our clinical community. It is important to interpret the results of this trial alongside those of the ethnographic study and process evaluation, 26,27 which together suggest that quality improvement programmes designed to implement complex care pathways require more resources, with dedicated time for clinical teams to focus on making change happen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings reveal that implementation of such an extensive care pathway was a more complex challenge than expected by our clinical community. It is important to interpret the results of this trial alongside those of the ethnographic study and process evaluation, 26,27 which together suggest that quality improvement programmes designed to implement complex care pathways require more resources, with dedicated time for clinical teams to focus on making change happen.…”
Section: Discussionmentioning
confidence: 99%
“…Our prospective ethnographic study and process evaluation are reported in full elsewhere. 26,27 The findings showed that teams reflected positively on the QI programme, in particular the practical nature of the activation and education meetings, and the opportunity to share ideas and learn from others as well as the utility of the online resources. However, staff in each of the six sites studied encountered multiple challenges as they attempted to improve patient care during the intervention period and often had little or no additional time in their job plans to accommodate this.…”
Section: Quality Improvement and Ethnographic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the QI intervention did not impact upon patient survival, EPOCH provided vital learning about how we can and cannot improve patient care using large-scale QI programmes. 20,21 ELC was a large QI project funded by the Health Foundation, adopting implementation science to improve patient care. 7 The project was led by the Kent Surrey Sussex Academic Health Science Network ( www.kssahsn.net ) in 28 NHS hospitals, and used a quality improvement collaborative model to help teams to implement a laparotomy care bundle.…”
Section: Three Major Initiatives To Improve Emergency General Surgerymentioning
confidence: 99%
“…To meet these challenges, broad stakeholder buy-in, organisational readiness and efficient use of scarce resources (funding and workforce) are necessary. [12][13][14] Ensuring fidelity refers to the delivery of interventions as designed and intended and applies particularly to complex multicomponent interventions such as the POPS service. Addressing these translational challenges is necessary to establish effective, efficient and equitable services for older surgical patients across the UK.…”
Section: Introductionmentioning
confidence: 99%